New Lived Spaces in the Post-industrial World: The Sound of Colors by Jimmy Liao - Leonor Ruiz-Guerrero (University of Bologna, 2019)
The post-industrial era brought new spaces whose lack of habitability soon led to call them non-places. These are transit spaces that often exceeded the human dimension, architectures that were frequently hostile to the body. Literature did not take long to incorporate them, also children's literature. Airports, train stations, subway, began to populate the pages of books for children. The Sound of Colors, by Jimmy Liao, is an example of this. In this paper, this book has been analyzed, with an attempt to show the complexity of author treatment of the space. In this picturebook, a blind girl faces the everyday life in the subway stations. The whole narrative is developed between two interconnected worlds, the real one depicted by this non-place, and the other, poetic, by the girl. A qualitative methodology has been employed to study this work. Findings lead to thinking that current children's literature spaces are increasingly multifaceted.